MEKANISME DAN EFEKTIVITAS BAKTERI FOSFAT DALAM PELEPASAN FOSFOR DI ANDISOL - , Tamad ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The phosphate bacteria (PB) has ability to release P-adsorped through its acidification, chelation, ligand exchange, mineralization and blocking of soils colloid adsorption site. The effective PB needs to be formulated in the form of inoculant as solution for Andisols which is one among soils with relatively low phosphorus (P) availability because of P is much adsorped by allophane. The research aims were to know the role of PB mechanism in releasing P-adsorped from Andisol through its anorganic-P solubilization, organic-P mineralization and blocking of Andisols adsorption site and to test the effectiveness of PB inoculant on Andisols with maize as indicator plant. The research was consisted of two experiment series. The first serie was to know the mechanism role of P released by PB which was elucidated through test of anorganic-P solubilization, organic-P mineralization and blocking for Andisols adsorption site. The second serie was to test PB effectiveness on Andisols and in vivo test. Phosphate bacteria isolate number 1 (Pseudomonas trivialis), 5 (P. putida) and 9 (P. fluorescens) was more able to solubilize P on Pikovskaya than others. Phosphorus solubilization by PB was in the order of CaP > phosphate rock (PR) > AlP > FeP, while amount of P mineralization by PB from P nitro phenyl phosphate (pNPP) and Na-fitat was not different. The PB inoculant which contented three isolates was more capable to release P-adsorped on Andisols. Phosphate bacteria inoculation for two weeks before P application significantly increased the release P-adsorped on Andisols. The inoculation of PB on Andisols increased the release P-adsorped which contribution of each mechanism was not different. The equation of P release by PB from Andisols was P-release (ppm P) = 1051.96 + 1.18 P-anorganic solubilization (ppm P) + 1.09 P-organic mineralization (ppm P) â 0.92 P-adsorped (ppm P) (R2= 0.99). The PB inoculation on Andisols with phosphate rock and compost applied effectively increased the release P. The PB inoculation on Andisols with phosphate rock applied enhanced maizeâs growth component, P content to normal level, P absorption, RAE (relative effectiveness agronomic) and P efficiency.